On Dinosaur Reconstruction: Posture of Dinosaurs - Florides, Georgios A.; Christodoulides, Paul (My University, 2021)
Dinosaurs due to their diverse species and peculiar forms have drawn the interest of both artists and scientists. One way to unlock the unknown life of dinosaurs is to reconstruct dinosaurs through drawings, computer animations or sculptures. Following the Introduction on “Dinosaur Reconstruction” by the present authors, where important Paleontological knowledge was presented, the next step is to examine some specific information along with necessary details for dinosaur reconstruction. The first and basic step to be taken for a reconstruction is the posture of the animal; this is the theme of the current paper. Dinosaurs would move either bipedally or quadrupedally depending on their kind and body construction. Based on the available literature, various issues in relation to the posture of an animal at different instances are examined. These are: postures of bipedal dinosaurs during walking, observation of living bipedal animals, postures of quadruped dinosaurs during walking, feeding styles, and dinosaur tails. Theropods had a locomotor behavior like modern birds, with the step width increasing when the animals decreased speed. The general posture and movement of quadrupeds and especially sauropods, remains a subject of great and much controversy. Some scientists believe that sauropod necks were generally held in a neutral or undeflected state during most of the time, while others believe that sauropod necks behaved like all present-day amniote with the mid-cervical region held nearly vertical. Also, there are indications that dinosaurs usually held their tails above ground. For all dinosaurs, the long tail was acting as a counterbalance to the head and body. As a validating example, the case of Amargasaurus is investigated with the help of a model, where the various positions of the animal are examined. A certain posture was chosen for a full-size steel and concrete reconstruction based on the features of the animal.
Keywords: Sauropod Locomotion; Dinosaur Postures; Necks and Tails; Theropod Locomotion; Dinosaur Modeling; Amargasaurus; Extinct Animals; Skeletal Reconstruction